Evaluation of hourly physico-chemical data between 2012 and 2015 from two permanent probes on the Berg River Estuary, Western Cape, South Africa - Cilliers, Gerhard (University of Pretoria, 2022)
Mini Dissertation (MSc (Water Resource Management))--University of Pretoria, 2021.